2000
DOI: 10.1038/35035131
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of oestrogen receptor with the regulatory subunit of phosphatidylinositol-3-OH kinase

Abstract: Oestrogen produces diverse biological effects through binding to the oestrogen receptor (ER). The ER is a steroid hormone nuclear receptor, which, when bound to oestrogen, modulates the transcriptional activity of target genes. Controversy exists, however, concerning whether ER has a role outside the nucleus, particularly in mediating the cardiovascular protective effects of oestrogen. Here we show that the ER isoform, ER alpha, binds in a ligand-dependent manner to the p85alpha regulatory subunit of phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
940
6
18

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,312 publications
(1,005 citation statements)
references
References 31 publications
41
940
6
18
Order By: Relevance
“…It is known that IGF-1R primarily activates the MAPK and PI3/Akt pathways and both of these signal transduction pathways phosphorylate the serine residue in the AF1 domain of the ER. 38,39 This synergy obviously is possible if both ER and IGF-1R are expressed by tumor cells. Interestingly, we have recently shown that IGF receptor 1 (IGF-1R) is expressed at a significantly higher level in all ER þ tumors (including ER þ /HER2 þ ) compared with ERÀ/HER2 þ tumors (Appl Immunohistochem Mol Morphol; in press).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that IGF-1R primarily activates the MAPK and PI3/Akt pathways and both of these signal transduction pathways phosphorylate the serine residue in the AF1 domain of the ER. 38,39 This synergy obviously is possible if both ER and IGF-1R are expressed by tumor cells. Interestingly, we have recently shown that IGF receptor 1 (IGF-1R) is expressed at a significantly higher level in all ER þ tumors (including ER þ /HER2 þ ) compared with ERÀ/HER2 þ tumors (Appl Immunohistochem Mol Morphol; in press).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, much evidence has shown that in multiple cell types under different experimental conditions, steroid receptors directly interact with several signaling effectors and trigger various biological effects. In addition to Src, these effectors include calmodulin (Castoria et al, 1988), the regulatory subunit of the phosphoinositide 3-kinase, p85a (Simoncini et al, 2000;Castoria et al, 2001), Shc (Song et al, 2002), modulator of non genomic activity of receptor (Wong et al, 2002), protein kinase Cz (Castoria et al, 2004), EGF receptor (Marquez et al, 2001;Migliaccio et al, 2005), and many other signaling or signaling-related proteins. Therefore, approaches similar to those followed in this report, that is, recognition of new receptor/signaling effector interactions and identification of new inhibitors of such interactions, could enable us to specifically inhibit different hormone actions mediated by signal transducing pathways in multiple cell types and in different pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, PTEN mutations also were found in receptor positive tumors, in keeping with the suggested role of the PTEN-PI3K-AKT pathway in ER regulation. 46 PTEN alterations have been linked to advanced disease in certain cancers 47 and through promoter region hypermethylation also linked to metastatic potential in endometrial carcinomas. 48 This suggests that PTEN inactivation is achieved through different mechanisms and that the biologic role of PTEN in endometrial carcinoma needs to be investigated further, preferably with tumors stratified for presence/absence of hyperplasia.…”
Section: Discussionmentioning
confidence: 99%